Impact of cognitive biases on environmental compliance risk perceptions in international construction projects - Chang, Tengyuan; Du, Yuxuan; Deng, Xiaopeng; Wang, Xianru (Frontiers in Psychology, 2024)
This research explores the complex interplay between cognitive biases and Environmental Compliance Risk Perception (ECRP) in international construction projects. Analyzing a scenario-based questionnaire survey conducted with 270 international construction practitioners, this study employs Partial Least Squares Structural Equation Modeling (PLS-SEM) to identify the influencing factors of cognitive biases and their impact on ECRP. It reveals that Cultural Bias (CuB), Confirmation Bias (CoB), and Short-Termism (ST) significantly influence ECRP, affected by a mix of individual, organizational, and project-specific factors. Based on these insights, the study proposes an innovative framework for evaluating ECRP and a management strategy aimed at recognizing and mitigating the cognitive biases of professionals during the bidding and execution phases of international construction projects. By elucidating the factors influencing cognitive biases and the complex relationship between cognitive biases and ECRP, this study underscores the significance of addressing employee cognitive biases, alongside enhancing environmental awareness, in environmental compliance management in international construction projects. It addresses a critical gap in the existing literature and provides international contractors with strategies for mitigating these biases in environmental compliance management. This, in turn, enhances the contractors' capabilities in environmental protection, reducing potential negative impacts on the environment from international construction projects, which is crucial for promoting sustainable development.